Perfectionism in “Perfect Slumber Party”, a Soundtrack of Sofia the First: the Big Sleepover (NOBEL: Journal of Literature and Language Teaching, 2021)
This study explores the representation established by “Perfect Slumber Party,” a soundtrack of Sofia the First: The Big Sleepover, on perfectionism, acceptance, and social equity. The representation of soundtrack seen from a musical meaning perspective is conducted by analyzing the diverse and subjective perspectives of ‘perfectionism’ among the born Royal, embodied by Princess Amber and her ally and the new princess, denoted by Princess Sofia. The finding shows that the music brings the debate between establishing and eliminating social classes based on the acceptance or rejection of non-perfection. Furthermore, the part of lyrics sung by Sofia reinforces her to be a bold and brave heroine delivering a positive message to the viewers.